2015
DOI: 10.1155/2015/373574
|View full text |Cite
|
Sign up to set email alerts
|

miR-193b Modulates Resistance to Doxorubicin in Human Breast Cancer Cells by Downregulating MCL-1

Abstract: MicroRNAs (miRNAs) family, which is involved in cancer development, proliferation, apoptosis, and drug resistance, is a group of noncoding RNAs that modulate the expression of oncogenes and antioncogenes. Doxorubicin is an active cytotoxic agent for breast cancer treatment, but the acquisition of doxorubicin resistance is a common and critical limitation to cancer therapy. The aim of this study was to investigate whether miR-193b mediated the resistance of breast cancer cells to doxorubicin by targeting myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…We propose that miR-193b inhibits a network of genes involved in the complex processes of VM and may be key in modulating tumour growth and development. Previously identified targets of miR-193b are limited, but include cyclinD1 and ETS1 in hepatoma cells 55 , uPA, HSP40 and RAB22A in MDA-MB-231 cells 39 , 52 and MCL-1 in MCF7 cells 72 . Further research is required to determine if other genes involved in the DDAH/ADMA/NO and associated pathways are also targets for miR-193b in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that miR-193b inhibits a network of genes involved in the complex processes of VM and may be key in modulating tumour growth and development. Previously identified targets of miR-193b are limited, but include cyclinD1 and ETS1 in hepatoma cells 55 , uPA, HSP40 and RAB22A in MDA-MB-231 cells 39 , 52 and MCL-1 in MCF7 cells 72 . Further research is required to determine if other genes involved in the DDAH/ADMA/NO and associated pathways are also targets for miR-193b in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In MDA-MB-231 cells, among upregulated miRNAs there are miR-26a, miR-149, miR-181a, miR-193b, miR-195 and miR-324-3p that increase drug responsiveness. In particular, previous studies showed that miR-26a sensitized gastric cancer to cisplatin targeting NRAS and E 2 F 2 [ 22 ], miR-149 increased chemosensitivity of glioblastoma to Temozolomide treatment through a RAP1B-mediated remodeling of cellular cytoskeleton [ 23 ], miR-181a enhanced Adryamicin-induced apoptosis targeting Bcl-2 [ 24 ], miR-193b sensitized cancer cells to Doxorubicin targeting myeloid cell leukemia-1 (MCL-1) [ 25 ], miR-195 increased Adriamycin sensibility by downregulating RAF [ 26 ], and, finally, miR-324-3p induced drug sensitivity reducing its SMAD7 target mRNA that is associated with lung, pancreas and skin cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…It drives urgent need to detect new targets and treatment strategies. MiRNAs play a vital role in tumorigenesis, angiogenesis and drug resistance [3234], and are proved to be a useful biomarker in the diagnosis and prognosis of cancer. Recently, miRNAs or anti-miRNAs trafficked by microvesicles (MV) or other plasmids have been used for the treatment of various diseases in mouse models, including cancers [22, 35, 36].…”
Section: Discussionmentioning
confidence: 99%